Cloud-based control system: a bibliometric analysis - Santo Wijaya; Harco Leslie Hendric Spits Warnars; Ford Lumban Gaol; Benfano Soewito (Universitas Ahmad Dahlan, 2022)
Network control system (NCS) approaches for distributed closed-loop control systems have been established in industrial control. However, recent advancements in cloud computing provide scalable, elastic, and low-cost networked computing capabilities over the internet, which can be utilized as an extension of NCS, in this term, cloud-based control systems (CCS) with a potential replacement of the controller. The main objective of this research is to use bibliometric analysis to obtain insight into diachronic productivity, the significant effect of the published information on the research network, and research trends based on term co-occurrences of the CCS domain. The literature study employs the PRISMA method to construct necessary inclusion criteria such as keywords, databases, publication year, accessibility, and primary article, then Publish or Perish is used to generate RIS formatted file for network analysis of co-authorship and term co-occurrence with VOSviewer. The results showed that Yuanqing Xia was the most prolific author in terms of the total published article and total citations received, China was the country with the highest publication output, and Elsevier was the publisher with the most significant impact factor. CCS emerged in 2012, and current research trends include control system architecture, controller, algorithm, stability, and approach on intelligent manufacturing.